Camera as short-term memory - Sim, Guo Ping. (2013)
The objective of this project is to develop an Android mobile application suitable for mobile devices using the Android operating system as a short-term memory aid with quick access as an alternative or replacement to the traditional method of writing or memorising the subject. Mobile devices with camera are chosen to be the replacement due to its availability and functionalities. The concept is to make use of the camera of a mobile device to quickly capture a photo or video to help users remember something or somewhere and provide a mean to swiftly access the file for reference. A policy this project coined as "no more than three clicks" policy is employed to ensure swift photo or video taking as well as viewing the multimedia file and it's information. The Global Positioning System (GPS) is also used to enhance the capability and information the application capable to keep track. The final product of this project has successfully achieved the objective by deploying the concept, policy and technology aforementioned.